2020
DOI: 10.3928/00220124-20200914-07
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Needs Satisfaction and Behavioral Intentions of Sexual Health Care

Abstract: Background: This study aimed to evaluate correlations between female nurses' needs satisfaction and behavioral intentions for providing sexual health care and to assess moderating effects of learning needs on that correlation. Method: A total of 300 female RNs were enrolled. Two validated instruments were used to collect information on participants' learning needs, needs satisfaction, and behavioral intentions for providing sexual health care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This finding is consistent with some studies that show service quality perception was a predictor of patient choice, 5 , 10 or patient satisfaction of service experience was an antecedent to behavioral intention. 35 , 36 This finding provides the foundation for our subsequent mediation analysis.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This finding is consistent with some studies that show service quality perception was a predictor of patient choice, 5 , 10 or patient satisfaction of service experience was an antecedent to behavioral intention. 35 , 36 This finding provides the foundation for our subsequent mediation analysis.…”
Section: Discussionmentioning
confidence: 67%
“…This finding is consistent with some studies that show service quality perception was a predictor of patient choice, 5,10 or patient satisfaction of service experience was an antecedent to behavioral intention. 35,36 This finding provides the foundation for our subsequent mediation analysis. We further found that the effect of quality perception on outpatients' choice outcome was fully mediated by the outpatient experience, which are consistent with studies in other contexts that indicated "satisfaction of service experience" as a good…”
Section: Discussionmentioning
confidence: 71%